The PKM: Enhancing the Capacity and Professionalism of the Merah Putih Cooperative through Business Proposal Writing Training in Lumika Village, Bonehau District, Mamuju Regency: PKM Meningkatan Kapasitas dan Profesionalisme Koperasi Merah Putih melalui Pelatihan Pembuatan Proposal Bisnis di Desa Lumika Kecamatan Bonehau Kabupaten Mamuju - DSA, Jeffriansyah; Mariam, Mariam; J, Rhena; Hajjad, Mu’fidatul Nurul; Yusuf, Andi Muhammad Ridho (Mattawang: Jurnal Pengabdian Masyarakat, 2025)
This community service program aims to enhance the capacity of the Merah Putih Cooperative in Lumika Village, Bonehau District, Mamuju Regency, through training in business proposal preparation. The program was implemented using a participatory approach involving needs identification, intensive training, and mentoring. The results showed a 42% increase in participants' understanding of proposal structure, financial projections, and loan simulation. Participants successfully drafted a comprehensive business proposal, including a three-year cash flow projection and a loan simulation of IDR 50 million with a flat interest rate of 6% per year. The activity proves that practice-based training can improve cooperative members' skills and strengthen their confidence in business management. This initiative also demonstrates the role of universities as catalysts for rural economic development through business literacy and cooperative governance.